Pengaruh Disiplin Kerja dan Kemampuan Komunikasi terhadap Kinerja Karyawan Sushigo Mall Central Park Jakarta Barat - Hasanah, Jihadah Putri; Syarifah Ida Farida (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of work discipline and communication skills on employee performance at Sushigo Mall Central Park, West Jakarta. The research used a quantitative associative approach with a saturated sample of 31 employees. Data were collected through questionnaires and analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination with SPSS. The results show that work discipline and communication skills have a positive and significant effect, both partially and simultaneously, on employee performance. These findings indicate that improving discipline and communication is essential to enhance employee performance.